Novel Polymer‐Based Organic/c‐Si Monolithic Tandem Solar Cell: Enhanced Efficiency using Interlayer and Transparent Top Electrode Engineering. Issue 17 (7th August 2021) - Park, HyunJung; Park, So Hyun; Lee, Sang‐Won; Kang, Yoonmook; Kim, Donghwan; Son, Hae Jung; Lee, Hae‐Seok
Abstract: Tandem solar cells which are electrically connected with various photoactive materials have the potential to solve the current challenges by exceeding the theoretically limited efficiency of single junction solar cells. Here the first monolithic organic/silicon tandem cell is reported based on a semitransparent polymer on a crystalline silicon (c‐Si) substrate. Herein, experimental results are presented for four‐terminal (4‐T) and monolithic two‐terminal (2‐T) organic/c‐Si tandem cells using organic cells with an inverted n‐i‐p structure and c‐Si cells with an n‐type TOPCon structure with detailed analysis. The best 4‐T tandem cell efficiency is 15.22%, and 2‐T results show that the top (organic) and bottom (c‐Si) cells are electrically connected by an open‐circuit voltage over 1.4 V. Further, a simulated efficiency of over 20% using the organic/c‐Si tandem is achieved, implying the tandem efficiency can be enhanced through further improvement of electric and optical characteristics with the optimization. Abstract : This study reports the first monolithic organic/c‐Si tandem solar cells using polymer photoactive materials on c‐Si wafer substrates. The each subcell is electrically connected by showing an open circuit voltage over 1.4 V, and the efficiency simulation results indicate the possibility of achieving over 20% efficiency using the organic/c‐Si tandem cells.